2012
DOI: 10.32635/2176-9745.rbc.2012v58n2.624
|View full text |Cite
|
Sign up to set email alerts
|

Desnutrição em Crianças até 12 Anos com Leucemia Atendidas no Grupo em Defesa de Criança com Câncer no Município de Jundiaí, SP

Abstract: Introdução: As neoplasias malignas merecem atenção especial, principalmente na infância, pois podem afetar o crescimento e desenvolvimento das crianças; além disso, existe um elevado risco dessas crianças apresentarem desnutrição, devido a vários fatores, como: os efeitos colaterais da terapia antineoplásica, a alteração psicossocial (depressão, ansiedade e medo), a insuficiente ingestão calórica e proteica. Objetivo: Identificar o estado nutricional de 42 crianças de zero a 12 anos de idade, o tipo de dieta p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
0
3
0
6
Order By: Relevance
“…Thirteen studies addressed nutritional status and body composition (Table 1). [14][15][16][17][18][19][20][21][22][23][24][25][26] Overall, the prevalence of underweight patients at diagnosis varied from 6% to 25% and during treatment from 10.5% to 52.4%. In patients with ALL, the most studied diagnosis, the prevalence of underweight varied from 6% to 21.2% at diagnosis, 19,[24][25][26] increasing to 52.6% in one study that assessed patients after at least one chemotherapy cycle.…”
Section: Results By Primary Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies addressed nutritional status and body composition (Table 1). [14][15][16][17][18][19][20][21][22][23][24][25][26] Overall, the prevalence of underweight patients at diagnosis varied from 6% to 25% and during treatment from 10.5% to 52.4%. In patients with ALL, the most studied diagnosis, the prevalence of underweight varied from 6% to 21.2% at diagnosis, 19,[24][25][26] increasing to 52.6% in one study that assessed patients after at least one chemotherapy cycle.…”
Section: Results By Primary Outcomementioning
confidence: 99%
“…In patients with ALL, the most studied diagnosis, the prevalence of underweight varied from 6% to 21.2% at diagnosis, 19,[24][25][26] increasing to 52.6% in one study that assessed patients after at least one chemotherapy cycle. 16 Stunting prevalence ranged from 8.9% to 42.9%, [14][15][16]22,24,25 and one good-quality study reported growth deficit during and several years after treatment, with a negative impact on the final height, particularly in children younger than 4 years of age and in those who received cranial irradiation. 26 Overweight and obesity, however, had a reported prevalence of 4.1%-35% at diagnosis, 19,20,23,26 and 7.2%-57.9% during or after treatment.…”
Section: Results By Primary Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…A leucemia é o tipo de câncer infantojuvenil mais comum entre crianças e adolescentes em todo o mundo, pois representa cerca de 30% de todos os tumores que ocorrem antes dos 15 anos. Além disso, observa-se um padrão quanto aos subtipos (LMA e LLA) em relação à idade, sendo a LMA mais frequente no primeiro ano de vida e a LLA mais comum na primeira infância (em torno de 80% de todas as leucemias nesta faixa etária), tendo como pico de incidência entre 2 e 5 anos, com predomínio do sexo masculino, corroborando com os achados deste e de outros estudos (16,14,15,17,18). Em outro estudo, realizado por Barreto et al (19) foram encontrados resultados semelhantes, no qual a maioria tinha o diagnóstico de LLA (45%) e eram do sexo masculino (56%), contudo a faixa etária que prevaleceu foi de 7 a 12 anos (59%).…”
Section: Discussionunclassified
“…No entanto, na pesquisa de Brinksma et al 9 , constatou-se que pacientes menores de 8 anos apresentaram maior prevalência de recusa alimentar, contrapondo-se ao estudo de Damasco-Ávila et al 8 . Caram et al 18 realizaram uma pesquisa com 31 pacientes oncológicos pediátricos, em que foi possível classificar a relação do peso por idade. Como resultados, crianças entre 3 e 6 anos de idade apresentaram baixo peso por conta da desnutrição, confirmando assim o estudo de Brinksma et al 9 .…”
Section: Discussionunclassified